Comment on “Philosophy of mind as a problem of philosophy and science: representatives of the west and east” - Vekluk, Anton (2023)
Commented Article reference: JALMAGAMBETOVA, Samal, GARIFOLLA, Yessim and NURYSHEVA, Gulzhykhan. Philosophy of mind as a problem of philosophy and science: representatives of the West and East. Trans/Form/Ação: Unesp journal of philosophy, Marília, v. 47, n. 2, “Feminine perspectives in philosophical thought”, e0240025, 2024.